Effect of Load Sequence and Weather Seasonality on Fatigue Crack Growth for Monopile-based Offshore Wind Turbines. (September 2016) - Ziegler, Lisa; Schafhirt, Sebastian; Scheu, Matti; Muskulus, Michael
Abstract: Offshore wind turbines are subjected to variable amplitude loading, but the impact of load sequence is commonly neglected in fatigue analysis. This paper presents an initial investigation if load sequence and weather seasonality influence fatigue crack growth for monopile-based offshore wind turbines. Focus is on the load sequence effect introduced by the non-linearity of crack propagation. Fatigue crack growth at two structural hot spots was analyzed with a fracture mechanics model applying Paris' law. The model was calibrated to yield an identical lifetime as a SN-curve analysis. Input into the fracture mechanics model are structural stresses due to environmental and operational loading. Weather seasonality was simulated with a Markov model. Results show that loading sequence has only a negligible effect on crack sizes under the assumption made in this study. This makes fatigue lifetime predictions independent of weather seasonality. However, it becomes relevant for the prediction of future propagation of detected fatigue cracks throughout the year.